The Implementation of Problem-Based Learning (PBL) Model to Improve Creativity and Self-Efficacy of Field Dependent and Field Independent Students - Maulidia, Farrah; Saminan, Saminan; Abidin, Zainal (Universitas Malikussaleh, Aceh Utara, Indonesia, 2020)
Students’ creativity and self-efficacy in solving mathematical problems remain low. Students with Field Dependent (FD) and Field Independent (FI) cognitive styleshave different creativity and self-efficacy. One learning model that is believed to increase students' creativity and self-efficacyis Problem Based Learning (PBL) model. This study aimed to increase the creativity and self-efficacyof FD and FI students through the application of PBLmodel. This research is an experimental study with pre-test and post-test control group design.The population of this research was grade VIII students in State Islamic School (MTsN) 1 Banda Aceh,while the sample consisted of two classes out of 11 classes. The sampling technique usedrandom samplingwith one experimental class and one control class. Data collection was carried out by using two instruments; a paper-test to measure students’ creativity and a questionnaire to measure students’self-efficacy. The grouping of FD and FI students was based on the results of the Group Embedded Figure Test (GEFT). Furthermore, a paired t-test was conducted to obtain an increase in students' creativity and self-efficacy. At the same time, a correlation test was performed to see the relationship between creativity and the self-efficacy ofstudents. The results of the study revealed that the increase of FD and FI students’ creativity who were taught by the PBL model was better than students taught by conventional methods. The results also reported that the increase of FD and FI students’ self-efficacy who were taught with the PBL model was better than the students who were taught with conventional methods. In addition, there was a significant relationship between FI and FD students' creativity and self-efficacy.